2015
DOI: 10.1038/srep17744
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and risk of subtypes of head-neck cancer: the Netherlands Cohort Study

Abstract: Low body mass index (BMI) has been associated with risk of head-neck cancer (HNC), but prospective data are scarce. We investigated the association between BMI, BMI at age 20 years and change in BMI during adulthood with risk of HNC and HNC subtypes. 120,852 participants completed a questionnaire on diet and other cancer risk factors, including anthropometric measurements, at baseline in 1986. After 20.3 years of follow-up, 411 HNC (127 oral cavity cancer (OCC), 84 oro-/hypopharyngeal cancer (OHPC), and 197 la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…Many of our results were consistent with those of the large cohort studies (33, 34) and pooled analysis of anthropometry and HNC (19) (the latter of which included data from an earlier follow-up of the EPIC cohort). The strength of the associations detected for BMI and WHR in relation to HNC risk in the NIH-AARP study, the largest single cohort study to date on this topic, (33) were broadly consistent with those reported in the present study for men; it is likely that their HNC cases were predominantly men, given a higher incidence of HNC among men and the higher proportion of men (60%) in the NIH-AARP cohort (33).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Many of our results were consistent with those of the large cohort studies (33, 34) and pooled analysis of anthropometry and HNC (19) (the latter of which included data from an earlier follow-up of the EPIC cohort). The strength of the associations detected for BMI and WHR in relation to HNC risk in the NIH-AARP study, the largest single cohort study to date on this topic, (33) were broadly consistent with those reported in the present study for men; it is likely that their HNC cases were predominantly men, given a higher incidence of HNC among men and the higher proportion of men (60%) in the NIH-AARP cohort (33).…”
Section: Discussionsupporting
confidence: 86%
“…The strength of the associations detected for BMI and WHR in relation to HNC risk in the NIH-AARP study, the largest single cohort study to date on this topic, (33) were broadly consistent with those reported in the present study for men; it is likely that their HNC cases were predominantly men, given a higher incidence of HNC among men and the higher proportion of men (60%) in the NIH-AARP cohort (33). As in the present study, the risk of HNC in the Netherlands Cohort Study (NLCS) was significantly higher among those with relatively low BMI values (34). However, further comparison of the results by smoking status is limited as there was no evidence of non-linearity between BMI and HNC risk in NLCS and therefore BMI analysed as a continuous variable among smoking subgroups.…”
Section: Discussionsupporting
confidence: 75%
“…Regarding UADT cancers, several case–control studies have suggested that low BMIs may enhance the effects of alcohol consumption on the risk of oral cavity and oropharyngeal cancer [4,25] ; however, prospective studies have not confirmed this joint effect. [11] Few studies have examined the joint effect on esophagus cancer or AUD.…”
Section: Discussionmentioning
confidence: 99%
“…[4,912] Additionally, associations between BMI and mortality from these alcohol-related diseases per se have not been clearly established. [911] A better understanding of the impact of alcohol consumption and body weight on these alcohol-related diseases may help physicians and health professionals in treating their patients and establishing strategies to reduce the burden of these diseases. We aim to evaluate whether alcohol consumption and BMI interact to increase the risk of death from these alcohol-related diseases, based on a study of middle-aged Korean men.…”
Section: Introductionmentioning
confidence: 99%
“…Types of cancer associated with leanness are known in people in general, although no such association has been reported in type 2 diabetic patients. The risk of development of cancer of the head and neck is reported to be negatively correlated with BMI. Renehan et al .…”
Section: Discussionmentioning
confidence: 99%